Robotic Anxiety-Parents' Perception of Robot-Assisted Pediatric Surgery - Elisabeth Ammer; Laura Sophie Mandt; Isabelle Christine Silbersdorff; Fritz Kahl; York Hagmayer (MDPI AG, 2022)
In contrast to many other countries, robot-assisted (RA) pediatric surgery is not yet very common in Germany. Although the first pediatric RA intervention was published in 2001, RA pediatric surgery is still perceived as a "new technology". As a consequence, little is known about parents' perception of this operation method. In this study, we analyzed parents' intention to let their child undergo RA and laparoscopic (LA) surgery. Two subsamples (online and at the University Medical Center Goettingen) received a questionnaire addressing attitude towards RA and LA pediatric surgery with the help of a case example. Results showed that parents had a higher intention to consent to LA surgery. Perceiving more benefits, assuming a positive attitude of the social environment, and feeling less anxiety increased intention. A mediation analysis indicated that the type of surgery affected intentions through assumed attitude of the social environment. Exploratory analyses showed that the perception of risks and anxiety reduced intention for only RA surgery. These findings should be considered in preoperational discussions with parents. Anxiety and perceived risks should especially be addressed in order to encounter hesitancy.